A retrospective drug utilization study in chemotherapy-induced nausea and vomiting - Aher, Ashwini A.; Razvi, S. U.; Baig, M. S. (International Journal of Research in Medical Sciences, 2025)
Background: Chemotherapy-induced nausea and vomiting (CINV) significantly impacts patients’ quality of life. Despite advancements in therapy, optimal management of CINV remains crucial. This study evaluates drug utilization patterns in CINV management in patients attending the government cancer hospital, Chhatrapati Sambhajinagar (Maharashtra). Objective were to evaluate the drug utilization patterns in CINV management amongst cancer patients. Methods: Retrospective, cross-sectional observational study in 242 cancer patients attending the outpatient department in a government cancer hospital, Chhatrapati Sambhajinagar. The prescriptions were taken from the record section after the necessary approval of IEC and permissions. Prescriptions were evaluated as per WHO drug prescribing indicators. Results: The 484 drugs were prescribed for CINV in 242 patients. Most patients were aged between 51-60 years (31.82%), followed by 41-50 years (26.86%). All drugs are prescribed under generic names. Three classes of drugs were identified as monotherapy or combination therapy. 5-HT3 receptor antagonists and corticosteroids were the two most frequently used classes, followed by NK1 receptor antagonists. In prescribing patterns, dual combination regimens of 5-HT3 receptor antagonists and corticosteroids were the most common (99.17%), followed by triple combination and monotherapy (0.41% each). Out of the total, 483 (99.79%) drugs were given by parenteral route and 1 (0.21%) by oral route. Conclusions: Following standard protocols for CINV was noted. The use of 5-HT3 receptor antagonists (Granisetron) and corticosteroids (dexamethasone) in combination was common, suggesting a pattern of adherence to guidelines and improving patient care.